2024
DOI: 10.1109/tem.2022.3153395
|View full text |Cite
|
Sign up to set email alerts
|

Chief Digital Officer and Organizational Creativity Toward Digitalization

Abstract: Through the microfoundation lens, this article explores how dynamic capabilities (DCs) of Chief Digital Officers (CDOs) trigger digitalization and organizational creativity of 2124 small to medium enterprises (SMEs) across 39 different European countries. As a result, the significant DCs are substantive and adaptive capabilities, which are offering new solutions, seizing new opportunities, and coping with changes. Besides, those two DCs also assume a mediator role in triggering organizational creativity within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…However, the digital servitization process is highly complex, and most manufacturers lag in their digital aspirations (Sj€ odin et al, 2020;Kohtam€ aki et al, 2019). On the other hand, companies that move towards digital servitization struggle with the business model complexities that digital servitization creates; such complexities include conflicts between digital and physical service offerings, seizing new opportunities and handling with clashes between new ecosystem partnerships and traditional supply chain relationships and specific knowledge management competencies in terms of business organization, understanding and fulfillment of customers' needs (Chen et al, 2021;Scuotto et al, 2022). In this scenario, it is possible to highlight companies, such as Volvo, that are rapidly moving to find more autonomous solutions in digital servitization (Parida et al, 2014;Kohtam€ aki et al, 2019;Porter and Heppelmann, 2014), but the role of knowledge in the digital servitization of inbound and outbound supply chains is still under-investigated.…”
Section: Supply Chain Digital Servitizationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the digital servitization process is highly complex, and most manufacturers lag in their digital aspirations (Sj€ odin et al, 2020;Kohtam€ aki et al, 2019). On the other hand, companies that move towards digital servitization struggle with the business model complexities that digital servitization creates; such complexities include conflicts between digital and physical service offerings, seizing new opportunities and handling with clashes between new ecosystem partnerships and traditional supply chain relationships and specific knowledge management competencies in terms of business organization, understanding and fulfillment of customers' needs (Chen et al, 2021;Scuotto et al, 2022). In this scenario, it is possible to highlight companies, such as Volvo, that are rapidly moving to find more autonomous solutions in digital servitization (Parida et al, 2014;Kohtam€ aki et al, 2019;Porter and Heppelmann, 2014), but the role of knowledge in the digital servitization of inbound and outbound supply chains is still under-investigated.…”
Section: Supply Chain Digital Servitizationmentioning
confidence: 99%
“…On the other hand, companies that move towards digital servitization struggle with the business model complexities that digital servitization creates; such complexities include conflicts between digital and physical service offerings, seizing new opportunities and handling with clashes between new ecosystem partnerships and traditional supply chain relationships and specific knowledge management competencies in terms of business organization, understanding and fulfillment of customers' needs (Chen et al. , 2021; Scuotto et al ., 2022). In this scenario, it is possible to highlight companies, such as Volvo, that are rapidly moving to find more autonomous solutions in digital servitization (Parida et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Leaders driving DT should be facilitators and communicators (Gilli et al, 2022;Magesa & Jonathan, 2021;Schiuma et al, 2021), creative and visionary (Gilli et al, 2022;Zhu, 2015), knowledge-oriented (Klein, 2020), collaborative (Gilli et al, 2022;Promsri, 2019), enthusiastic and motivator (Magesa & Jonathan, 2021) and should organize the change and increase the awareness related to the benefits of DT practices (Cichosz et al, 2020). Besides, innovativeness resulting in knowledge creation increased market accessibility, and new products/services are considered the most critical component of digital development (Magesa & Jonathan, 2021;Scuotto et al, 2022).…”
Section: Development Of Hypotheses and Research Modelmentioning
confidence: 99%
“…Thus, it indicates a total change and paradigm shift associated with strategy, vision, leadership, digital awareness and capabilities, and perceiving and capturing opportunities. Previously, it was reported that digital transformation provides competitiveness, increase in sales and revenue (Matt et al, 2015), supply chain efficiency (Accenture, 2017), cost reduction (Verhoef et al, 2021), better or improved productivity (Silva, 2017), and innovativeness and growth (Scuotto et al, 2022) for business enterprises. With Covid-19 uncertainties and disruptions in all business functions, it has become a survival issue for obvious reasons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation